Correcting Students’ Understanding about Simple Direct Current (DC) Circuits through Scientific Approach - Susi Marcelina; Theo Jhoni Hartanto (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2021)
This paper reports the effect of teaching electricity in simple DC circuits using a scientific approach on students’ understanding. The study was a pre-experimental design using 12 students. They were all studying in specific first secondary schools in the sub-urban area in Kasongan City, Katingan Regency, Central Kalimantan Province. This work used the multiple-choice tests to combine reasoning and certainty of response index (CRI). This test was used as pre and post-test, respectively, to assess students’ understanding of electricity in simple DC circuits. As a result, it is found that the secondary students have alternate conceptions about simple DC circuits, such as “electricity comes out of both ends of a cell” and “a circuit uses up the electric current”. On the other hand, the results of this study showed that the use of a scientific approach in learning could help students achieve conceptual change about electricity in simple DC circuits. The findings from the study suggested that there was a difference in students’ understanding of simple DC circuits between pre-test and post-test. The scientific approach to learning seemed to help students achieve conceptual change about electricity in simple DC circuits.